An Image Encryption Scheme of Logistic Modulation Using Computer-Generated Hologram and Chaotic Map - Hui Ren; Jun Wang; Qiong-Hua Wang (Journal of Electrical and Computer Engineering)
We introduce an image encryption method based on computer-generated hologram (CGH) and two-dimensional Sine Logistic modulation map (2D-SLMM). We combine CGH and 2D-SLMM to improve encryption security. During the encryption process, the hologram needs to be logistically modulated by 2D-SLMM. This logistic modulation technique can avoid complex algorithms. Simulation results and security analysis demonstrate that the proposed approach has a high security level, good invisibility of image information in ciphertext, large key space, and strong robustness.